Pengaruh Integrated Marketing Communication Terhadap Brand Equity Di Perbankan Syariah - Arnita Septiani Panjaitan; Sri Ramadhani; Muhammad Lathief Ilhamy Nasution (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine the effect of Integrated Marketing Communication on Brand Equity at PT. Bank Sumut Syariah Tebing Tinggi Branch Office uses Advertising, Direct Marketing, Sales Promotion, Public Relations, Events and experience variables. This study used a quantitative technique with a sample of 100 customers. The data analysis technique used in this study includes classic assumption testing and hypothesis testing whose test results are managed using the SPSS 22 program. The results of the study explain that advertising variables partially have a positive and substantial effect on brand equity, so direct marketing variables partially have a negative and substantial effect on Brand Equity. The sales promotion variable has a somewhat positive effect on Brand Equity. The public relations variable has a positive and significant effect on Brand Equity. Event and experience factors partially affect brand equity positively and significantly. Advertising, direct marketing, sales promotion, public relations, events and shared experiences (Test F) have a higher value on brand equity.